Review of international approaches to evaluating rural and community development investment and supports - Adele Whelan; Séamus McGuinness; Alan Barrett (The Economic and Social Research Institute (ESRI), 2021)
Evaluation and monitoring are key tools to ensuring that public monies are being effectively spent and that government-funded programmes, and initiatives, are achieving their stated goals and objectives. This report examines international best practice in evaluation and monitoring in areas relevant for the Department for Rural and Community Department (DRCD).
Keywords: 330